Social networks marketing, value co-creation, and consumer purchase behavior: Combining PLS-SEM and NCA - Farzin Arbabi; Seyed Mohammad Khansari; Salamzadeh Aidin; Abbas Gholampour; Pejman Ebrahimi; Maria Fekete-Farkas (Journal of Risk and Financial Management, 2022)
Given the mediating role of value co-creation, this paper tries to demonstrate how social network marketing (SNM) could influence consumer purchase behavior (CPB). The proposed hypotheses are empirically tested in this study using a PLS-SEM and Necessary Condition Analysis (NCA) method combination. The novel methodology adopted in this study includes the use of NCA, IPMA matrix, permutation test, CTA, and FIMIX. The assessment of the outer model, the inner model, the NCA matrix, and the IPMA matrix are the four steps that the paper takes. Instagram users with prior experience making purchases online made up the statistical population of the study. Four hundred twenty-seven questionnaires were analyzed by SmartPLS3 software. Based on the findings, SNM positively and significantly influenced economic, enjoyment, and relational values. Furthermore, these three types of values significantly and directly influenced CPB. For CPB, the model accounted for 73.8% of the variance. The model had high predictive power because it outperformed the PLS-SEM benchmark for all of the target construct's indicators in terms of root mean square error (RMSE). According to the NCA's findings, SNM, economic, recreational, and relational values are necessary conditions for CPB that are meaningful (d Ï 0.1) and significant (p < 0.05). Four prerequisites must be met for CPB to reach a 50% level: relational value at no less than 8.3%, enjoyment value at no less than 16.7%, economic value at no less than 33.3%, and SNM at no less than 31.1%. The highest importance score for SNM is shown to be 0.738, which means that if Instagram channels improve their SNM performance by one unit point, their overall SNM will also improve by 0.738.
Keywords: 650; social media; social networks marketing; value co-creation; consumer purchase behavior; Instagram